Decomposition of intensity of energy-related CO2 emission in Chinese provinces using the LMDI method. (May 2016) - Zhang, Wei; Li, Ke; Zhou, Dequn; Zhang, Wenrui; Gao, Hui
Abstract: Uncovering the driving factors of CO2 emission intensity declining is important for China. This paper improves the logarithmic mean Divisia index technique, which includes energy density and energy consumption intensity, to explore the driving factors of carbon emission intensity (CI) in 29 Chinese provinces from 1995–2012. The main results are: (1) energy consumption intensity plays a more important role than carbon emission density (CD) for a rapid decrease in CI during the research period, so a much room is left for a significant CD reduction through carbon emission reduction technology, energy structural reduction, and energy consumption proportional reduction. (2) The decrease in energy consumption technology and energy structure in secondary industries contributes the most reduction in energy consumption intensity. (3)The energy consumption proportions of secondary and tertiary industries are the two most important drivers to decrease CD. (4) During the research period, the energy consumption proportions of secondary industries result in the most decrease in CD, whereas the energy consumption proportions of tertiary industries cause the most increase in CD. Highlights: Carbon emission intensity decreased rapidly from 1995 to 2012. Energy intensity is the more significant driver for decrease of carbon intensity. The most contribution of EI's decrease came from secondary industries. The most contribution of CD's decrease came from secondary and tertiary industries. Several policies of reducing carbon emission intensity in China have been raised.